Relative age effect in olympic taekwondo athletes - Albuquerque, M. R.; Menezes Lage, G.; Teoldo da Costa, V.; Melo Ferreira, R.; Macedo Penna, E.; Couto de Albuquerque Moraes, L. C.; Malloy-Diniz, L. F. (Perceptual and Motor Skills, 2012)
Relative age effects refer to the effects of age differences among individuals who have been grouped together for a performance activity. This study aimed to investigate the relative age effect on Olympic Taekwondo athletes, in several Olympic Games, and in both sexes. The study sample consisted of 291 athletes who had competed in Atlanta, Sydney, and Beijing Olympic Games. The relative age effect was examined for the general distribution of athletes by quartile, for each of the individuals, and for male and female athletes. There were no discernable effects of relative age on Olympic Taekwondo athletes.